Analisis Komparatif Nilai N-SPT terhadap Klasifikasi Tanah Berdasarkan Sistem USCS - wahyuni, yayu sri; Hidayatulloh, Taufik (MoDuluS Media Komunikasi Dunia Ilmu Sipil, 2025)
This study aims to analyze the relationship and compatibility between the Standard Penetration Test (SPT) N-value and soil classification based on the Unified Soil Classification System (USCS). The SPT is commonly used to determine in-situ soil density and consistency, while the USCS provides a comprehensive classification of soil types through grain size distribution and Atterberg Limits parameters. Data were collected from six different depth intervals, consisting of N-SPT values, grain size analysis (gravel, sand, silt, clay), and Atterberg Limits (LL, PL, IP). The results indicate that all soil samples are classified as high-plasticity clay (CH) according to the USCS, characterized by Liquid Limit (LL) values ranging from 70.45% to 86.83% and Plasticity Index (PI) values from 38.91 to 49.26. The N-SPT values range from 2 to 21, representing soil conditions from very soft to medium dense. Despite the variation in N-SPT values, the soil classification remained consistently within the CH group, dominated by fine-grained materials with high plasticity. These findings suggest that the N-SPT values describe relative soil strength but are not sufficiently sensitive to reflect variations in fine-grained soil characteristics, which are primarily controlled by plasticity and mineral composition. The study concludes that the direct correlation between N-SPT values and USCS classifications is not linear for high-plasticity cohesive soils. Therefore, the interpretation of soil conditions in CH-type soils requires an integrated approach that combines field testing (SPT) with laboratory analyses (grain size and Atterberg Limits). This highlights the importance of a comprehensive geotechnical evaluation to achieve a more accurate understanding of soil behavior. Keywords:N-SPT, USCS, Atterberg Limits, grain size analysis, CH soil, soil classification.